Wealth transfer in forward property markets - Y. P. Leung, Barbara (International Journal of Strategic Property Management, 2010)
The principal‐agent problem arising from asymmetric information in presales of uncompleted properties in forward property markets has been well‐recognized. Since buyers are not able to inspect the uncompleted properties when they make the purchases, developers may hide information about the negative aspects of the properties or over‐state the quality in order to generate an extra profit in the presales on top of the equilibrium value as if the properties were sold in the spot market. In this regard, the study adapted a forward‐spot property repeat sales pricing model to explore the pricing of presale properties compared to that of spot properties in which the principal‐agent problem does not exist. The findings suggest that developers were able to impose a wealth transfer from the buyers in pricing presale properties taking the advantage of asymmetric information embedded in forward property markets.First Published Online: 09 Jun 2011